AHAMONIYLAR DAVLATINING BOSHQARUV TIZIMI: SATRAPLIK TIZIMI VA UNING AHAMIYATI - Amonova Sevinch Zamon qizi, Egamberdiyeva Shirin Ğulom qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article provides an overview of the Achaemenid Empire and describes the events that took place in this state. The Achaemenid Empire experienced numerous wars, and the article analyzes the events that followed these wars. The impact of these wars on the political and social structure of the empire, as well as the consequences for its future, is thoroughly examined.